Components of Excellence and its Effects on Developing Achievement and Attitude in Mathematics among Secondary School Students - Othman A. Alghtani (Sultan Qaboos University, 2015)
The study aimed to build a suggested strategy in light of Connectivism theory to develop the components of excellence in mathematics, and measure its effect on developing achievement and attitude among secondary school students. The study depended on the experimental design, two groups (pre-post); also the sample was selected randomly among first grade students in secondary school. The unit quadrilaterals have prepared in using proposed strategy. The instrument of study included: questionnaire of components of excellence in mathematics, achievement test, and questionnaire of attitude. The main findings were there are significant differences between the average grades of the experimental and controlling group in post application of questionnaire of excellence, achievement test and attitude questionnaire in favor of the experimental group students. In light of the results, the recommendations were including: applying connectivism theory in teaching mathematics to develop components of excellence in mathematics. All of these points have supported developing achievement and attitude toward mathematics.